Evaluating the disaster preparedness of emergency medical services (EMS) facilities: a cross-sectional investigation in Iran - Mehdi Beyrami Jam; Mohsen Aminizadeh; Yousof Akbari-Shahrestanaki; Hamid Reza Khankeh (BMC Emergency Medicine, 2024)
Abstract Introduction The preparedness of Emergency Medical Services (EMS) plays a crucial role in managing health disaster risks. This study was conducted to assess the disaster preparedness of EMS facilities in Iran, using a nationally reliable tool. Methods A cross-sectional study was conducted in May 2021 to evaluate the disaster preparedness of EMS facilities in Iran using a national standard tool. The census sampling approach was utilized to select the samples, and descriptive statistics, as well as analytical statistics like the independent t-test and Pearson’s correlation test, were used to analyze the data using SPSS-18 software. Results The findings of this study revealed that the majority of EMS facilities in Iran possess a moderate level of preparedness in dealing with disasters. Also, the results indicate that EMS facilities have an average level of preparedness against disasters in all dimensions except for “coordination and cooperation” and “surge capacity”. Conclusion According to this study, the majority of EMS facilities in Iran are exposed to different disasters. Furthermore, the findings indicate that while EMS facilities are generally prepared to respond to disasters at an average level, there are some important preparedness gaps in dimensions like response capacities, coordination, and cooperation. Thus, specific strategies, standards, and procedures must be developed and disseminated by the National Medical Emergency Organization.